1971
DOI: 10.1071/bi9710331
|View full text |Cite
|
Sign up to set email alerts
|

Some Biochemical and Kinetic Properties of Sheep Uterine Endometrial Alkaline Phosphatase

Abstract: Ab8tractSheep uterine endometrial alkaline phosphatase in a purified state displayed optimal activity at pH 10·5. At pH 9· 0 activity increased with decreasing substrate concentration.The enzyme catalysed the hydrolysis of a variety of phosphomonoesters and exhibited pyrophosphatase properties when incubated with ADP and ATP. Metalcomplexing agents, such as EDTA, NaCN, o-phenanthroline, and L-cysteine inhibited the phosphatase while Mg2+ stimulated its activity. Recovery of activity was both rapid and complete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

1979
1979
2021
2021

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 8 publications
2
2
0
Order By: Relevance
“…The dependence of optimum pH for activity on substrate concentration together with decreases in the value of the apparent Km with decreasing pH are findings which are also in agreement with reports on other alkaline phosphatases (Harkness 1968;Hiwada and Wachsmuth 1974;Lopez et al 1976;Van Belle 1976;Adler 1978) and support the proposal that the enzyme may be catalytically active under physiological conditions of pH and substrate concentration (Morton 1957;Harkness 1968;Murdoch 1971). Furthermore, like other alkaline phosphatases (Fernley 1971) the enzyme in the present study was stable in neutral or mildly alkaline solution but was inactivated at pH 5· O.…”
Section: Arrhenius Plot and Activation Energysupporting
confidence: 79%
“…The dependence of optimum pH for activity on substrate concentration together with decreases in the value of the apparent Km with decreasing pH are findings which are also in agreement with reports on other alkaline phosphatases (Harkness 1968;Hiwada and Wachsmuth 1974;Lopez et al 1976;Van Belle 1976;Adler 1978) and support the proposal that the enzyme may be catalytically active under physiological conditions of pH and substrate concentration (Morton 1957;Harkness 1968;Murdoch 1971). Furthermore, like other alkaline phosphatases (Fernley 1971) the enzyme in the present study was stable in neutral or mildly alkaline solution but was inactivated at pH 5· O.…”
Section: Arrhenius Plot and Activation Energysupporting
confidence: 79%
“…The ability of Mg2+ ions to stimulate the activity of purified preparations of mouse uterine alkaline phosphatase without influencing K m values or the response of the enzyme to changes in temperature is consistent with observations on phosphatases from other sources (Murdoch 1971;BruneI and Cathala 1973;Linden et al 1977;Jung and Pergande 1979). In addition, like other alkaline phosphatases (Ackerman and Ahlers 1976;Chlebowski et al 1979), the uterine enzyme requires zinc to maintain structural stability (present study).…”
Section: Discussionsupporting
confidence: 91%
“…Although buffer effects of a similar nature have been described by other investigators (see Rej 1977), satisfactory reasons to explain them have not been found (Ghosh et al 1977). The effects of Mg2+ ions on the orthophosphatase and pyrophosphatase activities of the uterine enzyme are also similar to those described for other phosphatases (Murdoch 1971;Seargeant and Stinson 1979). These observations support the view that pyrophosphatase behaviour is activated by low concentrations of Mg2 + when the complex ion MgP 20 7 2 -is available as substrate but is progressively inhibited as the Mg2 + to pyrophosphate concentration ratio is increased and a Mg2P20 7 complex is formed (see Nayudu and Miles 1969).…”
Section: Discussionmentioning
confidence: 59%
“…G6P is a slower substrate than pNPP and Pi will form faster in the latter reaction. 31 Although we observe enzyme aggregation with both substrates, the aggregation is immediate for pNPP (Figure 4B) but starts at around 6 minutes for G6P (Figure 4C), when compared to AkP without substrate (Figure 4A), further supporting that Pi is the aggregator. Again, the presence of zinc ions is necessary for the aggregation to occur.…”
Section: Resultsmentioning
confidence: 51%